WEB DEVELOPMENT - SINGH, AARTI; ANIKESH, ANANYA (IJRDO -Journal of Computer Science Engineering, 2016)
The web-technology is going through major changes these years, both with respect to types ofsystems based on web-technology, organization of the development work, requiredapproaches and competencies, etc. We must rethink the organization of the developmentwork. This requires a deeper and coherent understanding of the nature of web-development.This paper presents findings from a field study undertaken in a web-developmentcompany.Web development is a broad term for the work involved in developing a web site forthe Internet (World Wide Web) or an intranet (a private network). Web development canrange from developing the simplest static single page of plain text to the most complex webbasedinternet applications, electronic businesses, and social network services. A morecomprehensive list of tasks to which web development commonly refers, may include webdesign, web content development, client liaison, client-side/server-side scripting,webserver and network security configuration, and e-commerce development. Among webprofessionals, "web development" usually refers to the main non-design aspects of buildingweb sites: writing markup and coding.This paper focuses on web devlelpoment areas of webdevelopment future scope of web development